Bee-ing similar: low diversity, no population structure, and signals of adaptation in two North Dakota bumble bees - Rhiannon Hall; Meggan A. Alston; Jason P. Harmon; Clint R. V. Otto; Travis Seaborn (Biodiversity and Conservation, 2026)
Habitat fragmentation and destruction are driving widespread declines in ecosystem function, species abundance, and genetic diversity across the globe. Among the affected taxa are bumble bees (genus Bombus ), which are essential pollinators. Bumble bee declines have been linked to anthropogenic pressures such as land-use change and climate change. To better understand how the environment is shaping bumble bee populations, we employed a landscape genetics approach to examine the genetic diversity, population structure, and potential local adaptation of two widespread species— Bombus ternarius and Bombus griseocollis —across North Dakota. From 2017–2020, 161 B. ternarius and 200 B. griseocollis bumble bees were sampled in ND across 13 and 17 sites, respectively. We found low levels of heterozygosity and inbreeding across all populations for both species, with no evidence of population structure or isolation by distance. Our results revealed signatures of potential local adaptation to climatic variables and land cover characteristics, suggesting that our species are adapted to environmental gradients across the state. Having similar results between both species across all analyses suggests that other wide-ranging bumble bees in the region may share these patterns. High connectivity can buffer short-term population losses, but low genetic diversity may constrain adaptive potential and reduce resilience to future environmental change and emerging threats. Our findings have broad applicability to other pollinators and taxa facing similar environmental pressures. Both species have populations that continually exchange genes creating widespread connectivity but are still locally shaped by adaptation.

Unraveling microclimate effects on pollinator foraging and crop yield in lowbush blueberry - Garrett Sisk; Anaís Ostroski; Travis Dillard; Bruce Hall; Sarah C. Goslee; Christina M. Grozinger; Vikas Khanna; Heather Grab (Agriculture, Ecosystems & Environment, 2025)

Prevalence of osteosarcoma and investigation of risk factors in military working dogs: a retrospective study using data from the Deceased Military Working Dog Database - Alicia Moreau; Justin G. Bergeron; Kelsey Fiddes; Anna-Maria Travis; Sharon Daye; Amy K. LeBlanc; Jessica A. Beck; Terra D. Vincent-Hall; Elise LaDouceur (Journal of Comparative Pathology, 2025)

Water temperature and season length interact to explain a rare non‐linear ecogeographic cline in body size - Savanna Carlyn Barry; Matthew Denman Smith; Berlynna Heres; Travis Michael Thomas; Brittany J. Hall‐Scharf; H. Jane Brockmann (Journal of Biogeography, 2024)
Aim Adult body size often exhibits patterns across large‐scale environmental gradients, creating ecogeographic clines. However, the form of body size clines varies across taxonomic groups, with linear and non‐linear patterns in body size observed in nature. Non‐linear body size clines have received less study, and questions remain about how environmental gradients interact to produce non‐linear clines. We examined the body size of the American horseshoe crab ( Limulus polyphemus ), a widely distributed marine arthropod, and evaluated the hypothesis that temperature and active season length can interact multiplicatively to result in a dome‐shaped distribution. Location Fourteen states in the United States of America and three Mexican states, representing the entire geographic range of the species. Methods We compiled environmental data and body size measurements from more than 49,000 individual horseshoe crabs. For each location, we extracted from the literature or calculated from raw data the mean male prosoma width and the mean female prosoma width. We applied a general additive modelling (GAM) approach to characterize the body size cline, test a hypothesis regarding temperature and season length, and explore evidence for the influence of additional environmental factors. Results Model results indicate temperature and season length could act multiplicatively to produce dome‐shaped clines, and these findings align with and quantify previous anecdotal reports of a strong dome‐shaped body size cline across latitude for horseshoe crabs. Main Conclusions Active season length appears to become relatively more influential on horseshoe crab body size in the northern part of their range, while temperature effects per se appear to dominate in southern latitudes. For horseshoe crabs, the pattern of size variation is consistent with the predictions of Optimal Resource Allocation models, but more study is needed to elucidate mechanistic underpinnings. Considering climate change projections, results from our study suggest future shifts in horseshoe crab body sizes.

Simian varicella virus open reading frame 63/70 expression is required for efficient virus replication in culture - Elizabeth Brazeau; Mary Wellish; Benedict B. Kaufer; B. Karsten Tischer; Wayne Gray; Fuchun Zhou; Nikolaus Osterrieder; Teri Hanlon; Anjani Golive; Travis Hall; Sreekala Nair; Gregory P. Owens; et al. (Journal of NeuroVirology, 2011)

Historical Ecology as a Tool for Assessing Landscape Change and Informing Wetland Restoration Priorities - Eric D. Stein; Shawna Dark; Travis Longcore; Robin Grossinger; Nicholas Hall; Michael Beland (Wetlands, 2010)